The validity of the acoustic breathiness index in the evaluation of breathy voice quality: A Meta-analysis - Latoszek, Ben Barsties von; Kim, Geun-Hyo; Hernández, Jonathan Delgado; Hosokawa, Kiyohito; Englert, Marina; Neumann, Katrin; Hetjens, Svetlana (Clinical otolaryngology, 2021)
Background The evaluation of voice quality with acoustic measurements is useful to objectify the diagnostic process. Particularly, breathiness was highly evaluated and the Acoustic Breathiness Index (ABI) might have promising features. Objective of review The goal of the present meta-analysis is to quantify, from existing cross-validation studies, the evidence for the diagnostic accuracy of ABI, including its sensitivity and specificity. Type of review Meta-analysis. Search strategy We searched in MEDLINE, Google Scholar and Science Citation Index, and as manual search for the term Acoustic Breathiness Index from inception to February 2020. Studies were included that used equal proportion of continuous speech and sustained vowel segments, a recording hardware with a sufficient standard for voice signal analyses, the software Praat for signal processing and the customised Praat script, and two groups of subjects (vocally healthy and voice-disordered). Furthermore, the diagnostic accuracy of ABI was measured. Evaluation method The primary outcome variable was ABI. The score ranged from 0 to 10 with varying thresholds according to different languages to determine the absence or presence of breathiness. A meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses of diagnostic test accuracy study guidelines. Data were extracted, and the risk of bias was assessed using the QUADAS-2 tool. The pooled sensitivity and specificity of ABI were determined using a summary receiver operating characteristic (SROC) approach to calculate also a weighted threshold value of ABI with its sensitivity and specificity. Results A total of 34 unique citations were screened, and 10 full-text articles were reviewed, including six studies. In total, 3603 voice samples were considered for further analysis separating into 467 vocally healthy and 3136 voice-disordered voice samples. The pooled sensitivity was 0.84 (95% CI, 0.83-0.85), and the pooled specificity was 0.92 (95% CI, 0.89-0.94). The area under the curve of the SROC curve of this analysis showed an excellent value of 0.94. The weighted ABI threshold was determined at 3.40 (sensitivity: 0.86, 95% CI, 0.84-0.87.; specificity: 0.90, 95% CI 0.88-0.92). Conclusions The results confirm the ABI as robust and valid objective measure for evaluating breathiness.